The WHO Healthy Cities project realisation in Poland in last few years - Kapka, Lucyna; Cyranka, Małgorzata; Szymańska, Jolanta; Krasowska, Ewelina; Skrzypczak, Maciej (Polish Journal of Public Health, 2010)
The WHO Healthy Cities project is a global movement. It engages local governments in health development through a process of political commitment, institutional change, capacity-building, partnership-based planning and innovative projects. About 90 cities are members of the WHO European Healthy Cities Network, and 30 national Healthy Cities networks across the WHO European Region have more than 1,400 cities and towns as members. The Healthy Cities movement promotes comprehensive and systematic policy and planning for health. The Healthy Cities concept focuses on the process, not just the outcome. The article describes how Poland pursues the project and summarizes the Polish healthy cities network activity in implementing strategies to develop health in cities.